Two truths and a lie : it's alive! - Paquette, Ammi-Joan; Thompson, Laurie Ann (Walden Pond Press, an imprint of HarperCollinsPublishers, 2017)
Did you know that there is a fungus that can control the mind of an ant and make it do its bidding? Would you believe there is such a thing as a corpse flower -- a ten-foot-tall plant with a blossom that smells like a zombie? How about a species of octopus that doesn't live in water but rather lurks in trees in the Pacific Northwest? Every story in this book is strange and astounding. But not all of them are real. Just like the old game in this book's title, two out of every three stories are completely true and one is an outright lie. Can you guess which? It's not going to be easy. Some false stories are based on truth, and some of the true stories are just plain unbelievable. And they're all accompanied by dozens of photos, maps, and illustrations. Amaze yourself and trick your friends as you sort out the fakes from the facts!